Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 6 - Algebra: Equations and Inequalities - 6.1 Algebraic Expressions and Formulas - Exercise Set 6.1: 27

Answer

-12

Work Step by Step

Given -5$x^{2}$ - 4x -11, x=-1 Step 1: Put the value of x=-1 for each x in the expression =-5$(-1)^{2}$ - 4(-1) -11 Step 2: Evaluate the exponential expression$(-1)^{2}$ = (-1)(-1) = 1 =-5( 1)-4(-1)-11 Step 3: Multiply -5(1) = -5 and 4(-1)= -4 =-5 +4 -11 Step 4: Add and Subtract from left to right first add -5+4 -1-11 subtract -12
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.